1984
DOI: 10.1139/f84-019
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Dissolved Organic Carbon, Nutrients, and Trace Metals from the Wilson and Blossom Rivers to Smeaton Bay, Southeast Alaska

Abstract: Regional and seasonal differences in chemical input from the Wilson and Blossom rivers, two pristine, major salmon-producing rivers in southeast Alaska, were examined. For a period of 2 yr, concentrations of dissolved organic carbon, nutrients, Cu, Fe, and Mn in the rivers were determined at approximately monthly intervals and used to calculate export rates. Because of extremely high annual precipitation (400–450 cm) and drainage basins restricted by high topographical relief, the concentrations and export rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…Reports of the influence of spawning salmon on DON concentrations are rare. However, our finding that DOC concentrations were significantly higher in the spawning reach of Peterson Creek compared with the upstream reach differs from previous studies that have shown no significant increase in DOC associated with spawning salmon (Sugai and Burrell 1984;Chaloner et al 2004;Mitchell and Lamberti 2005). A study on spawning Chinook salmon in a Lake Ontario stream did find that concentrations of DOC were significantly correlated with salmon carcass density (Sarica et al 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Reports of the influence of spawning salmon on DON concentrations are rare. However, our finding that DOC concentrations were significantly higher in the spawning reach of Peterson Creek compared with the upstream reach differs from previous studies that have shown no significant increase in DOC associated with spawning salmon (Sugai and Burrell 1984;Chaloner et al 2004;Mitchell and Lamberti 2005). A study on spawning Chinook salmon in a Lake Ontario stream did find that concentrations of DOC were significantly correlated with salmon carcass density (Sarica et al 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study convincingly shows that, across streams in the Juneau area and in mesocosm streams, NH and SRP concentrations in ϩ 4 streamwater increase on average 10-and 3-fold, respectively, in the presence of spawning salmon, whereas NO and DOC western Washington stream. Sugai and Burrell (1984) observed a fivefold increase in both NH and SRP during the spawning likely was the result of the combination of salmon excretion while alive and tissue decomposition after death. Previous studies have shown that the prominent nutrients in fish excretion are NH and SRP (Meyer and Schultz 1985; ϩ 4 Brabrand et al 1990).…”
Section: Discussionmentioning
confidence: 94%
“…A week or two later, levels of ammonium and soluble reactive phosphorus (SRP) in stream water further increase, probably leached from carcasses or gametes released during spawning activities. As salmon continue to die and biomass from the carcasses is processed by consumer or microbial activity, SRP and NH 4 + increase but then decrease as the number of fish in the stream declines (e.g., Brickell andGoering 1970, Sugai andBurrell 1984). Finally, when only the skeletal tissue remains, P and Ca in the bones are the primary nutrients left.…”
Section: Dispersal Pathwaysmentioning
confidence: 99%